Hyporheic transport and biogeochemical reactions in pool‐riffle systems under varying ambient groundwater flow conditions. Issue 5 (27th May 2014) - Trauth, Nico; Schmidt, Christian; Vieweg, Michael; Maier, Uli; Fleckenstein, Jan H.
Abstract At the interface between stream water, groundwater, and the hyporheic zone (HZ), important biogeochemical processes that play a crucial role in fluvial ecology occur. Solutes that infiltrate into the HZ can react with each other and possibly also with upwelling solutes from the groundwater. In this study, we systematically evaluate how variations of gaining and losing conditions, stream discharge, and pool‐riffle morphology affect aerobic respiration (AR) and denitrification (DN) in the HZ. For this purpose, a computational fluid dynamics model of stream water flow is coupled to a reactive transport model. Scenarios of variations of the solute concentration in the upwelling groundwater were conducted. Our results show that solute influx, residence time, and the size of reactive zones strongly depend on presence, magnitude, and direction of ambient groundwater flow. High magnitudes of ambient groundwater flow lower AR efficiency by up to 4 times and DN by up to 3 orders of magnitude, compared to neutral conditions. The influence of stream discharge and morphology on the efficiency of AR and DN are minor, in comparison to that of ambient groundwater flow. Different scenarios of O2 and NO3 concentrations in the upwelling groundwater reveal that DN efficiency of the HZ is highest under low upwelling magnitudes accompanied with low concentrations of O2 and NO3. Our results demonstrate how ambient groundwater flow influences solute transport, AR, and DN in the HZ. Neglecting groundwater flow in stream‐groundwater interactions would lead to a significant overestimation of the efficiency of biogeochemical reactions in fluvial systems.